CORPORATE INSURANCE: COMPETITION FROM CAPITAL MARKETS AND FINANCIAL INSTITUTIONS - Doherty, Neil A. (Assurances, 1997)
Traditionally, the term "risk management" has been used to refer to the management of the downside risk that is usually associated with insurance. During the 1960's and 1970's, it became popular for corporate insurance buyers to frame the insurance decision as part of a wider process of managing risk. Many financial instruments have then emerged. The success of insurers in staving off competition from capital markets will rest on how effectively they reduce transaction costs. Certainly, unboundling allows insurers to target firms according to their particular needs. For firms that are large and publicly traded, the risk reduction offered by insurance is modest and expensive and the ancillary services provided by insurers are of limited value. However, there is a large demand for conventional insurance products from small firms, for whom the hedging and ancillary services of insurance will continue to be of value.